Improving safe post-abortion care practices: A study on interventions implemented by Ipas Pakistan - Arshad, Amna; Aziz, Hina; Shabbir, Ghulam; Shakya, Sagun; Munir, Zarnab (Frontiers in Public Health, 2023)
An estimated 50 million induced abortions occur in developing countries annually, and an estimated 7 million women are treated for complications associated with unsafe abortions. According to a 2012 estimate, 15 per 1,000 women aged 15–49 years seek treatment for abortion-related health complications in both private and public sectors. A high unmet need for family planning in Pakistan and a low percentage of women adopting a contraceptive method in the post-partum period led to unwanted pregnancy becoming one of the reasons for unsafe abortion. Post-abortion care (PAC) is an integrated service delivery model that includes both maternal health and family planning interventions. The study aims to examine improvement in abortion-related practices through the implementation of the PAC model at all tiers of public health service delivery systems in the two most populous provinces—Punjab, Sindh, Khyber Pakhtunkhwa, and Islamabad Capital Territory (ICT) region—of Pakistan. The improvement model comprises clinical training of healthcare providers, community engagement, and counseling of community women on safe post-abortion practices. It was a descriptive study utilizing data of 27,616 PAC clients recorded and reported by the service providers on the logbooks from 104 selected public health facilities from March 2018 to December 2021 in ICT, Punjab, Sindh, and Khyber Pakhtunkhwa provinces of Pakistan. Women who received PAC services were older than 25 years, 22,652 (82%), with a mean age of 29 years. Most of these women were in their first trimester, 26,110 (95%), and the majority diagnosed with PAC (incomplete, missed, or threatened abortion), 26,838 (97%). The majority of women, 25,324 (92%), received safe methods for post-abortion care that included the use of misoprostol, 15,804 (58%), and manual vacuum aspiration, 8,898 (32%). In total, 17,105 (72%) of women opted for a contraceptive method that included long-acting reversible contraceptives, 2,313 (10%); short-term excluding condoms, 3,436 (27%); and condoms, 8,113 (34%). The key predictors identified for uptake of the post-abortion family planning method indicated that women more than 25 years of age, in the early second trimester, and who were counseled on post-abortion family planning were more likely to adopt the contraceptive method than others. Increased access to post-abortion care and family planning could potentially reduce the incidence of unsafe abortion, unintended pregnancies, and associated maternal mortality. The experience of Pakistan suggests that the integrated post-abortion care service delivery model can be effectively implemented across the public health systems.